KONTRIBUSI DAYA LEDAK OTOT TUNGKAI TERHADAP KETEPATAN SHOOTING SEPAKBOLA PADA SISWA EKSTRAKURIKULER DI SMA NEGERI 2 BANGKINANG KABUPATEN KAMPAR - Ade Prasetyo, Kurniawan; Henjilito, Raffly (INSPIREE: Indonesian Sport Innovation Review, 2020)
The purpose of the study. To know the Contribution of Limb Muscles to the Accuracy of Shooting Football. Materials and methods. The sample in this study amounted to 20 male students. The leg muscle explosive power measurement test can be tested through the standing broad jumps test, whereas Football Shooting can be tested through a shooting test. Results. The contribution obtained from the formula KD = r2x100%, where the results of the search for correlation (r) are entered in the formula KD = 0.5152 x100% KD = 0.2652 x100% KD = 26.52% to find the correlation percentage. Where the rxy (0.515) >rtabel (0.444) is obtained, it can be said that there is a correlation and this proves that the presence of good leg muscle explosive power can produce shooting accuracy. Conclusions. There is a Contribution of the Explosive Power of the Legs to the Accuracy of Shooting Football in the Extracurricular Boys of SMA Negeri 2 Bangkinang, Kampar Regency